Effect of mutations and variations of HLA-A2 on recognition of a virus peptide epitope by cytotoxic T lymphocytes. - McMichael, A J (1988)
Cytotoxic T lymphocytes (CTL) specific for influenza A virus were prepared from 15 donors. Those with HLA-A2 recognized autologous or HLA-A2-matched B-lymphoblastoid cells in the presence of synthetic peptide representing residues 55-73 or 56-68 of the virus matrix protein sequence. Influenza A virus-specific CTL from donors without HLA-A2 or with an HLA-A2 variant type failed to respond to this peptide. CTL lines specific for HLA-A2 plus peptide did not lyse peptide-treated target cells from HLA-A2 variant donors. They also failed to lyse peptide-treated cells with point mutations that had been inserted into HLA-A2 at positions 62-63, 66, 152, and 156 and, in some instances, mutations at positions 9 and 70. CTL lysed peptide-treated target cells with mutations in HLA-A2 at positions 43, 74, and 107. The results imply that this defined peptide epitope therefore interacts with HLA-A2 in the binding groove so that the long alpha-helices of HLA-A2 make important contact with the peptide at positions 66, 152, and 156. Different amino acids at position 9, which is in the floor of the peptide binding groove of HLA-A2 and the closely related position 70, modulate the peptide interaction so that some T-cell clones react and some do not.